Two cases of severe hypothyroidism: myxedema coma - Basak, Ramen C; Basak, Mira (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Myxedema coma is a severe life-threatening form of decompensated hypothyroidism which is associated with a high mortality rate. It is characterized by altered mental status, hypothermia, hypotension, hyponatremia, and hypoventilation. Infections and discontinuation of thyroid supplements are the major precipitating factors. Here, two cases of severe hypothyroidism are described. Although they were neither in ‘coma’ nor represent typical ‘myxedema’, both had altered mental status and lethargy along with typical sign-symptoms of hypothyroidism. Morbidity and mortality from myxedema coma are frequently due to a missed or delayed diagnosis. Early disease diagnosis and intensive supportive care have reduced the mortality rate. However, as the disease is rare and unrecognized, evidence-based treatment of myxedema has not yet been established in many countries. J Assoc Clin Endocrinol Diabetol Bangladesh, January 2022; 1 (1): 31-34